Silent hunter - Mindscape (Firm). (Sunnyvale, CA Mindscape, 1996)
A role-playing World War II submarine simulator adventure game. Allows the player to choose from a variety of American submarines, prowl the shipping lanes, and steel into enemy harbors. Includes authenic WWII film footage, cinematics, and narration that provide a historically accurate feel for submarine combat. Play historical missions, hypothetical encounters or a career based campaign game.
Title from disc label.
System requirements: 486DX/66 MHz IBM PC or compatible; 8MB RAM; MS-DOS 6.0-6.22; uncompressed hard drive with 22MB free for small install; 1MB SVGA graphics with a color SVGA monitor; 2X speed CD-ROM drive (350 ms access and 300KB transfer rate); 100% Microsoft (or Logitech) compatible mouse; Microsoft mouse driver 9.0 or higher, or Logitech mouse driver 6.24 or higher.
Keywords: Computer adventure games -- Software